New Perspectives on Human Sacrifice and Ritual Body Treatments in Ancient Maya Society - Tiesler, Vera; Cucina, Andrea (Interdisciplinary Contributions to Archaeology, 2007)
Human sacrifice among the ancient Maya is a topic of widespread interest. It has triggered awe and romanticism in the general public, which often leads to unfounded myths misjudgments. This book dispels those myths by bringing together an international group of both well-established scholars and accredited young experts in the field to provide a fresh, objective look at ritual violence in the Mayan realm from an academic perspective. These experts offer examine new evidence of of human sacrifice in Classic and Postclassic period sites like Calakmul and the Sacred Cenote of Chichen Itz, as well as cave contexts from Belize. The contributions analyze meanings, agents, occasions, and sacrificial procedures, along with post-sacrificial body processing. They address questions about the recognition and interpretation of ancient Mayan sacrificial behavior with a multidisciplinary approach. Generalized issues of provenance and the social and health status of sacrificial victims are presented, as well as a joint discussion that gives the work an updated, Continental scope. This will be of interest to students studying Mayan and Mesoamerican culture as well as those interested in bioarchaeology and human sacrifice.